AI MONITORING AND MOBILE APPLICATIONS FOR PATIENT COMPLIANCE AND ORAL HEALTH IN ORTHODONTICS: A NARRATIVE REVIEW - Stopa, Ewa; Borek, Natalia; Gałązka, Julia; Miśkiewicz, Emilia; Krupa, Hanna; Wieczorek, Zofia; Pochwalski, Jakub; Kędrak, Magdalena; Stanisławski, Dominik; Jabłońska-Trzosek, Wiktoria (International Journal of Innovative Technologies in Social Science, 2026)
This narrative review synthesizes the current evidence on the role of artificial intelligence monitoring tools and mobile applications in orthodontics, focusing on oral health outcomes, behavioral changes, and clinical efficiency. A literature search was performed in PubMed/MEDLINE, Scopus, and Google Scholar for articles published in English between 2016 and 2026. Following purposive selection, 17 articles were included in this synthesis. Digital health interventions consistently improve patient compliance, including appointment attendance, appliance wear duration, and oral hygiene. Effectiveness varied by intervention design, with multimedia and gamified approaches showing consistent benefits, whereas simple text reminders produced mixed results. AI-powered platforms reduce the need for in-office visits while maintaining clinical oversight, although the evidence certainty remains low. Important considerations include data privacy, digital equity, and cost-effectiveness, which remain largely unaddressed in the literature. Digital health interventions, including mobile applications and AI-powered monitoring platforms, show promise as supplementary tools for personalized orthodontic care, with evidence of improvements in patient compliance and oral hygiene, although they are limited by study heterogeneity. The effectiveness of these interventions appears to vary according to the intervention design and patient characteristics. Future research should prioritize long-term randomized trials, platform comparisons, and cost-effectiveness analyses to guide the clinical implementation of these technologies.